Kepuasan Pengunjung yang dipengaruhi Daya Tarik Wisata dan Persepsi Harga melalui Lifestyle - Hasudungan, Revalino Tigor (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study explores Visitor Satisfaction influenced by Tourist Attractions and Price Perceptions through Lifestyle. The location of this study was a tourist destination called Taman Impian Jaya Ancol in August 2024. The study population consisted of 115 respondents willing to complete the questionnaire. Sampling using the accidental sampling method after being reduced by 20 respondents for validity and reliability testing. Ninety-five respondents were used to calculate multiple linear regression using the SPSS software application. The findings are as follows: directly, tourist attractions and price perceptions affect lifestyle, tourist attractions, price perceptions, and lifestyle affect the satisfaction of visitors to Taman Impian Jaya Ancol. Indirectly: tourist attractions and price perceptions affect visitors' satisfaction with Taman Impian Jaya Ancol through lifestyle.